Ancient gene duplications in RNA viruses revealed by protein tertiary structure comparisons. Issue 1 (10th March 2021) - Cisneros-Martínez, Alejandro Miguel; Becerra, Arturo; Lazcano, Antonio
Abstract: To date only a handful of duplicated genes have been described in RNA viruses. This shortage can be attributed to different factors, including the RNA viruses with high mutation rate that would make a large genome more prone to acquire deleterious mutations. This may explain why sequence-based approaches have only found duplications in their most recent evolutionary history. To detect earlier duplications, we performed protein tertiary structure comparisons for every RNA virus family represented in the Protein Data Bank. We present a list of thirty pairs of possible paralogs with <30 per cent sequence identity. It is argued that these pairs are the outcome of six duplication events. These include the α and β subunits of the fungal toxin KP6 present in the dsRNA Ustilago maydis virus (family Totiviridae ), the SARS-CoV ( Coronaviridae ) nsp3 domains SUD-N, SUD-M and X-domain, the Picornavirales (families Picornaviridae, Dicistroviridae, Iflaviridae and Secoviridae ) capsid proteins VP1, VP2 and VP3, and the Enterovirus (family Picornaviridae ) 3C and 2A cysteine-proteases. Protein tertiary structure comparisons may reveal more duplication events as more three-dimensional protein structures are determined and suggests that, although still rare, gene duplications may be more frequent in RNA viruses than previously thought. Keywords : gene duplications; RNA viruses.